Miso Soup Consumption Enhances the Bioavailability of the Reduced Form of Supplemental Coenzyme Q10 - Michiyo Takahashi; Mayumi Nagata; Takehiko Kaneko; Toshikazu Suzuki (Journal of Nutrition and Metabolism)
Coenzyme Q10 (CoQ10) is an essential compound that is involved in energy production and is a lipid-soluble antioxidant. Although it has been proposed as an antiaging and a health-supporting supplement, its low bioavailability remains a significant issue. Concurrent food intake enhances the absorption of orally administered CoQ10, but it has not been fully established whether specific food substances affect intestinal CoQ10 absorption. Therefore, to determine whether the bioavailability of supplemental CoQ10 is affected by diet, P30, a granulated and reduced form of CoQ10, was dispersed in four different foods, clear soup, miso soup, milk soup, and raw egg sauce. Those foods which contained CoQ10 were consumed on different occasions at intervals of 6–14 weeks by the same participants. Thirteen participants were recruited in the single-dose and repeated clinical study. When miso soup containing P30 was provided, the serum CoQ10 concentration increased faster than when participants consumed other P30-containing soups or a P30-containing raw egg sauce. The area under the curve for serum CoQ10 during the first 5 h after consumption of the P30-containing miso soup was approximately 1.5 times larger than those after the consumption of other P30-containing meals. These data imply that the absorption of CoQ10 supplements can be enhanced by consuming them with food and in particular with specific food substances, such as miso soup.